2006
DOI: 10.1128/mcb.00913-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the Trapα/Ssr1 Gene, Encoding Translocon-Associated Protein α, Results in Outflow Tract Morphogenetic Defects

Abstract: Translocon-associated protein complex (TRAP) is thought to be required for efficient protein-specific translocation across the endoplasmic reticulum membrane. We created a mutation in the Trap␣ gene that leads to the synthesis of a truncated TRAP␣ protein fused to ShBle-␤-galactosidase. Analysis of Trap␣ cDNAs reveals that among three different messenger RNAs expressed in the mouse, one of them encodes a slightly larger protein that differs in its C-terminal end. This mRNA, specific for skeletal muscle and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…SSR1, regulated by miR-4521, was associated with the pathway of protein processing. SSR1/Trapα, which may have a general role in protein translocation [39], was found involved in mammalian heart development [40]. Moreover, miR-4521 was found involved in cancer pathogenesis [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…SSR1, regulated by miR-4521, was associated with the pathway of protein processing. SSR1/Trapα, which may have a general role in protein translocation [39], was found involved in mammalian heart development [40]. Moreover, miR-4521 was found involved in cancer pathogenesis [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Insertional mutation of Trap-a, which encodes the a subunit, resulted in serious growth retardation with severe cardiac defects in mouse embryos from E14.5 and the mutant pups died at birth (Mesbah et al, 2006). By contrast, Trap-g LacZ/LacZ embryos did not show such severe growth retardation and cardiac defects and they were still alive at birth (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…S1). Absence of Trap-a also influences substrate-specific protein secretion so that secretion of gamma interferon and atrial natriuretic peptide are impaired, but preprolactin is not, in Trap-a À/À embryonic fibroblasts (Mesbah et al, 2006). This also suggests that individual TRAP subunits might have a distinct function in protein translocation and/ or modification in a substrate-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that SSr1 plays a crucial role in mammalian heart development and may be involved in the translocation of factors necessary for the maturation of endocardial cushions. For example, homozygous SSR1 mutant pups die at birth, possibly as a result of severe cardiac defects (18). NDRG2 is one of the four members of the new ndrG (n-myc downstream-regulated gene) family (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%